2014
DOI: 10.1097/01.prs.0000438454.29980.f8
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Amifostine Preserves the Biomechanical Properties of Irradiated Bone in the Murine Mandible

Abstract: Background The authors have previously demonstrated that amifostine prophylaxis mitigates the pernicious effects of radiation in settings of fracture repair and distraction osteogenesis. Expanding on these studies, the authors examined the biomechanical properties of uninjured bone exposed to both radiation and amifostine. The authors hypothesize that radiation will degrade the biomechanical properties of native bone, and further hypothesize that prophylactic amifostine will preserve biomechanical properties t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…According to Nyaruba et al (21) and Wernle et al (22), alterations in bone strength seem to be more related to changes in the trabecular morphology than in the cortical morphology of irradiated bone. Nevertheless, the influence of ionizing radiation on the mechanical properties of bone was not yet fully clarified, as there are conflicting reports in previous studies (11,(21)(22)(23). In addition, the micro-CT images (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Nyaruba et al (21) and Wernle et al (22), alterations in bone strength seem to be more related to changes in the trabecular morphology than in the cortical morphology of irradiated bone. Nevertheless, the influence of ionizing radiation on the mechanical properties of bone was not yet fully clarified, as there are conflicting reports in previous studies (11,(21)(22)(23). In addition, the micro-CT images (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In search to reduce bone damage due to irradiation, Rocha et al (8) and Freitas et al (9) observed a radioprotective effect of sodium selenite on bone healing in rat tibia, and Felice et al (11) noted radioprotective effects of amifostine on bone strength in rat mandible. However, in this study as in others (5-7), was chosen to evaluate the NSAID meloxicam as a radiationprotective agent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amifostine prophylaxis, however, also maintained native bone structure to the level of the nonirradiated controls 8 weeks after radiation. 27 Furthermore, amifostine pre-treatment preserved bone mineralization to the level of the nonirradiated control 18 weeks following radiotherapy, as there was no statistical difference between the mineral density levels and mineral to collagen ratios between groups. 27 , 28 These results, corroborated with micro-CT analysis, demonstrated that amifostine prophylaxis maintained mineralization metrics (BVF, BMD, and TMD) of irradiated bone to that of the nonirradiated controls.…”
Section: Pharmaceutical and Cellular-based Therapeuticsmentioning
confidence: 88%
“…Previous studies (3,15,(16)(17)(18) have sought to develop a model for induction of osteoradionecrosis in animals, through bone physiological changes with ionizing radiation; however, only a few have sought to evaluate means to prevent the development of the same. Moreover, although some experimental studies have studied the effect of radioprotective agents on the injuries of ionizing radiation (6,10,(19)(20)(21), their search was made with the goal to prevent or reduce acute complications of high doses of ionizing radiation. According to our knowledge, only one study (3) was found in the literature in which it was used a substance (a non-steroidal anti-inflammatory drug) with the aim to prevent or minimize chronic complications caused by ionizing radiation.…”
Section: Discussionmentioning
confidence: 99%